Identification of absorbed constituents and in vivo metabolites in rats after oral administration of Physalis alkekengi var. franchetii by ultra‐high‐pressure liquid chromatography quadrupole time‐of‐flight mass spectrometry. (8th November 2017) - Feng, Xinchi; Huo, Xiaoguang; Liu, Hongxia; Chai, Liwei; Ding, Liqin; Qiu, Feng
Abstract: The calyces of Physalis alkekengi var. franchetii (Chinese Lantern, JDL) are well‐known as traditional Chinese medicine owing to its various therapeutic effects. However, the bioactive constituents responsible for the pharmacological effects of JDL and their metabolites in vivo are still unclear to date. In this paper, an ultra‐high‐pressure liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry (UHPLC/Q‐TOF‐MS/MS) method was established to identify absorbed constituents and in vivo metabolites in rat biological fluids after oral administration of JDL. Based on the proposed strategy, 33 compounds were observed in dosed rat biosamples. Twelve of 33 compounds were indicated as prototype components of JDL, and 21 compounds were predicted to be metabolites of JDL. Finally, the metabolic pathways were proposed, which were glucuronidation, sulfation, methylation and dehydroxylation for flavonoid constituents and sulfonation and hydroxylation for physalin consitituents. This is the first systematic study on the absorbed constituents and metabolic profiling of JDL and will provide a useful template for screening and characterizing the ingredients and metabolites of traditional Chinese medicine.